Postharvest Processing of Millets: Advancements & Entrepreneurship Development Opportunities - Gopika Dinesh; Aparna S. Krishna; Yaghuvendra Kumar; T. Jayasree Joshi; P. Srinivasa Rao (Future Postharvest and Food)
ABSTRACT Millets, a member of the Poaceae family, are renowned for their significant nutritional value. In light of the increasing concerns surrounding climate change, millets offer a promising solution for the global population due to their exceptional ability to tolerate various abiotic stresses, such as drought, salinity, light, and heat. Additionally, millets have short growing periods and can thrive in adverse weather conditions with minimal irrigation requirements. It is essential to process millets before consuming them to extend their shelf life and improve their nutritional and sensory characteristics. The postharvest processing of millets encompasses both primary and secondary processing operations. However, the need for appropriate processing machinery and the short shelf life of millet flour caused by high lipid levels and enzymatic activity pose significant challenges in millet processing. These limitations can be addressed by employing suitable processing methods. Furthermore, there is ample opportunity for entrepreneurship in millet processing and value addition. Potential areas for exploration include the development of value‐added processing technologies, diversification of processing technologies, and expansion of machinery for commercial production in food markets. This article provides insights into advancements in millet processing and entrepreneurial technologies.